Hiding in Plain Sight: A Fourth New Cryptic Species of the Adenomera andreae Clade (Anura: Leptodactylidae) from Southwestern Amazonia - De Carvalho, Thiago R. [UNESP]; Angulo, Ariadne; Barrera, Diego A.; Aguilar-Puntriano, César; Haddad, Célio F.B. [UNESP] (Herpetologists League, 2020)
We describe a new species of Adenomera from southwestern Amazonia. The new species corresponds to one of the acoustic patterns and morphotypes from Tambopata National Reserve (Adenomera Forest Call II), which was associated with the candidate species identified via molecular data as Adenomera sp. C in the phylogeny of the genus. The new species is distinguished from all congeners, except A. phonotriccus, by a unique advertisement call: Calls are composed of complete pulses, i.e., separated by silent gaps, whereas those of remaining Adenomera species are composed of incomplete pulses (partly fused) or nonpulsed calls. The new species occurs in southeastern Peru and north central Bolivia, with two sympatric records with A. chicomendesi. The taxonomic status of two candidate species (sp. D and sp. T) of the A. andreae clade in southwestern Amazonia still needs to be addressed by the acquisition of additional phenotypic and molecular data.
Keywords: Acoustic diagnosis; Bioacoustics; Biodiversity; Peruvian Amazon; Tambopata National Reserve